Cervical Spine Immobilization in Patients With a Geriatric Facial Structure: The Influence of a Geriatric Mandible Structure on the Immobilization Quality Using a Cervical Collar - Jung, Matthias K.; Grützner, Paul A.; Schneider, Niko R.E.; Keil, Holger; Kreinest, Michael (Geriatric Orthopaedic Surgery and Rehabilitation, 2021)
Introduction: Demographic changes have resulted in an increase in injuries among geriatric patients. For these patients, a rigid cervical collar is crucial for immobilizing the cervical spine. However, evidence suggests that patients with a geriatric facial structure require a different means of immobilization than patients with an adult facial structure. This study aimed to analyze the remaining motion of the immobilized cervical spine based on facial structure. Materials and Methods: This study was performed on 8 fresh human cadavers. Facial structure was evaluated via ascertaining the mandibular angle by computer tomography. A mandibular angle below 130°, belongs to the adult facial structure group (n = 4) and a mandibular angle above 130°, belongs to the geriatric facial structure group (n = 4). The flexion and lateral bending of the immobilized cervical spine were analyzed in both groups using a wireless motion tracker system. Results: A flexion of up to 19.0° was measured in the adult facial structure group. The mean flexion in the adult vs. geriatric facial structure groups were 14.5° vs. 6.5° (ranges: 9.0-19.0 vs. 5.0-7.0°), respectively. Thus, cervical spine motion was (p = 0.0286) significantly more reduced in the adult facial structure group. No (p = 0.0571) significant difference was oberserved in the mean lateral bending of the adult facial structure group (14.5°) compared to the geriatric facial structure group (7.5°). Conclusion: Emergency medical service personnel should therefore follow current guidelines and recommendations and perform cervical spine immobilization with a cervical collar, including in patients with a geriatric facial structure.
CRIS-Team Scopus Importer:2021-06-18
Keywords: cervical collar; cervical spine; geriatric facial structure; immobilization quality